Elections, economic development and debt servicing in Africa - Serebour Quaicoe (Cogent Economics & Finance, 2023)
Despite the growing public debate on fiscal surprise during election periods in jurisdictions where the democratic dispensation is young, comprehensive empirical works to this effect in the case of Africa are hard to find. This study, therefore, sought to contribute to the debate on two counts. First, the study examines the effect of elections on debt servicing in Africa. Second, the study investigates the joint effect of economic development and elections on debt servicing in Africa. Using data drawn from the World Bank's World Development Indicators over the period 1985-2015 for 43 African countries, the study provides evidence from the dynamic system GMM and the ordinry least squares estimators to show that- (1) election periods are associated with lower debt servicing in Africa, and (2) economic development is significant in enhancing debt servicing commitments even in election periods. Policy recommendations are provided in line with the growing levels of debt accumulation and unemployment in Africa.
Keywords: E62; H6; O23; O55; P0; 330; Africa; budget cycle hypothesis; debt servicing; democracy; economic development; election; government expenditure